Blade-pitch system for tidal current turbines with reduced variation pitch control strategy based on tidal current velocity preview. (January 2018) - Gu, Ya-jing; Lin, Yong-gang; Xu, Quan-kun; Liu, Hong-wei; Li, Wei
Abstract: A collective pitch control system is designed using a rack and pinion gear set and hydraulic drive to provide an available blade pitch angle from 0° to 180°. This response accounts for the tidal current bi-directionality caused by flood and ebb under the moon's gravitational force. A front-installed hydraulic cylinder drives the rack-and-pinion system to synchronously turn the blades. Mechanisms are designed to overcome the difficulties of an outer hydraulic oil being deposited into the rotary hub and the pitch angle detection in a rotary hub. This simple and compact structure in a narrow hub reduces current blocking. Experimental results demonstrate that the pitch system has excellent dynamic characteristics. A tidal current velocity preview (CVP) method is proposed to overcome the difficulty of current velocity detection at the rotary impeller. Sealing is important for these underwater conditions. Hence, a reduced variation pitch control strategy is proposed based on CVP to reduce pitch action, which decreases mechanical wear of the sealing structure while extending the tidal current turbine's working life. Comparative results are obtained by using both an approximate sinusoidal current velocity data set simulating periods of real flow and a sea trial measured data set containing highly-turbulent and velocity-sheared flow in a semi-physical test. This test validated the significant reduction of pitch action and relatively high efficiency for energy generation. Highlights: A collective blade-pitch system is designed for tidal current turbines to capture bi-directional tidal current energy. A tidal current velocity preview (CVP) method is proposed to measure the current velocity at a rotary impeller. A reduced variation pitch control strategy is proposed based on CVP to reduce pitch action and decrease sealing wear. Relatively high efficiency of energy generation is maintained.